CONDITIONS PROBLEMS, AND GUIDELINES FOR THE MANAGEMENT OF MEN’S FOOTBALL TEAM IN HIGHER EDUCATION INSTITUTIONS: A CASE STUDY OF SURINDRA RAJABHAT UNIVERSITY - Meecharoen, Kittisak; Prachanban, Sathin; Malarat, Anan (Journal of Buddhist Anthropology, 2022)
The objectives of this research article were: 1) to study conditions, problems, and men’s football management in higher education institutions: a case study of Surindra Rajabhat University; and 2) to study the guidelines for the management of men's football in higher education institutions: a case study of Surindra Rajabhat University. This present study divided into 5 steps as follows. 1) Documentary studies relate to a sports managment in higer education institutions. 2) 20 participants who are successfull froml men’s football teams in the University Games of Thailan in the name of autonomous and private universities were purposively invited to participate a sem-structured interview. 3) 18 of stakeholders concerening a management of Surindra Rajabhat University’s men football team were purposively invited to participate a semi-structured interview. 4) 12 external experts concerning a management of Surindra Rajabhat University’s men football team were purposively invited to participate a semi - structured interview. 5) The results of 1 - 4 stepts were summarized and synthesized using content analysis and analytic induction techniques. The study found that: 1) Surindra Rajabhat University has operated the men's football team management, but there is no clear policy and organization. Further, inadequate budgeting and welfare, and unplan for the selection of athletes are still the problems. Moreover, oher problems are the unstandard training field, impersonnel in operation, and lack of cooperation from all sectors. 2) According to the guidelines for the management of men's football team, it is recommended that there should be a direct organizational structure for the management of men's football team in the form of a board with cooperation from all sectors. In addition, a fan base from the community and local should be built to develop together as the whole system.